CRITÉRIOS COMPETITIVOS DE OPERAÇÕES AGROINDUSTRIAIS: UM ESTUDO DE CASO NO SETOR ARROZEIRO - Fernandes Pacheco Dias, Marcelo (2013)
In recent years, rice processing firms have been characterized by a situation of poor economic performance and low competitiveness. This article seeks to discuss how the strategic management of operations can contribute to change this reality. Since in this sector the market is generally treated as homogenious, it is intended, by means of a case study, to identify all the competitive criteria that can be valued by the customers. The main goal is to identify the operations-based competitive criteria found in the literature and adapt them to the rice agroindustrial sector, taking its specificities into account. The results indicate the existence of several sector specific criteria and that price is still considered the most important criterion in almost all customer segments. A global analysis of the competitive criteria of the different market segments revealed opportunities to formulate synergistic operations strategies in order to compete in several different market segments.